Moderated by gender and generation: Innovation on firm performance in SME’s - Susanti, Nora; Yasri, Yasri; Patrisia, Dina (International Journal of Innovative Research and Scientific Studies, 2025)
This research aims to analyze the performance of SMEs in West Sumatra and how these SME actors understand and carry out innovations that are moderated by generation and gender. This study uses the resource-based view (RBV) theory and the theory of economic development (Schumpeterian theory). This research is a survey-based quantitative study. The sample for this research was 110, taken from several regions in West Sumatra. The data analysis technique used in this research is Structural Equation Modeling (SEM). The research results show that innovation has a significant effect on firm performance. In addition, gender does not strengthen or weaken the effect of innovation on company performance. Innovation on firm performance is moderated by gender and does not have a significant effect. Generations moderate innovation in firm performance and have a significant influence. In this context, generations do not weaken but instead strengthen innovation on SMEs' performance when viewed from the perspective of generation as a moderating variable, which has significant implications. Different generations within SMEs may influence the way innovation is implemented and the extent to which innovation impacts firm performance.